Artificial intelligence, education and the question about ends - García-Carreras, Aurora (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
This paper brings a discussion about the problem of artificial intelligence in the educational field. The approach seeks to unify both reflections on the possibilities of technology and education. To do this, in the first place, we wonder about the effective meaning of the expression "artificial intelligence" as well as the problems it raises in the field of discussion. Next, a critical analysis of the possible antecedents of the educational project incorporating artificial intelligence is carried out. Later the plurality of purposes and techniques of this tool are discussed. The latter leads us to a brief consideration of the role of humanistic reflection in this context.